Adlocution in French and Malay in parallel - Metzger, Laurent (Universiti Kebangsaan Malaysia, 1978)
In this article we would like to point out problems faced by the speaker when he wants to address someone either in Malay or in French. Four main areas have been considered, these are: the royal area, the literary area, the political area and daily conversation. We will try to explain how speakers solve these problems in the two languages.